2013
DOI: 10.1371/journal.pone.0057735
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Role of Nanoencapsulated Quercetin in Combating Ischemia-Reperfusion Induced Neuronal Damage in Young and Aged Rats

Abstract: Cerebral stroke is the leading cause of death and permanent disability among elderly people. In both humans and animals, cerebral ischemia damages the nerve cells in vulnerable regions of the brain, viz., hippocampus, cerebral cortex, cerebellum, and hypothalamus. The present study was conducted to evaluate the therapeutic efficacy of nanoencapsulated quercetin (QC) in combating ischemia-reperfusion-induced neuronal damage in young and aged Swiss Albino rats. Cerebral ischemia was induced by occlusion of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(90 citation statements)
references
References 49 publications
3
86
0
1
Order By: Relevance
“…5,29 The molecular weights of resulting PARP fragments are indicative of participation of a specific protease. Consistent with previous findings, 30 we found elevated cleaved-to-uncleaved PARP ratios in whole-brain lysates prepared from animals subjected to hypoxic insult (1 hour, 6% O 2 ) and reoxygenated for 10 minutes, 30 minutes, and 1 hour as compared with these same ratios in brain lysates from normoxic animals ( Figures 1A and 1B). The PARP fragments detected (i.e., 89 kDa) were consistent with those produced by executioner caspases.…”
Section: Hypoxia/reoxygenation Modulates Blood Gas and Circulating Elsupporting
confidence: 92%
“…5,29 The molecular weights of resulting PARP fragments are indicative of participation of a specific protease. Consistent with previous findings, 30 we found elevated cleaved-to-uncleaved PARP ratios in whole-brain lysates prepared from animals subjected to hypoxic insult (1 hour, 6% O 2 ) and reoxygenated for 10 minutes, 30 minutes, and 1 hour as compared with these same ratios in brain lysates from normoxic animals ( Figures 1A and 1B). The PARP fragments detected (i.e., 89 kDa) were consistent with those produced by executioner caspases.…”
Section: Hypoxia/reoxygenation Modulates Blood Gas and Circulating Elsupporting
confidence: 92%
“…194 Nanosizing quercetin greatly increases bioavailability and increases the protective effect at the target site without much loss in the gastrointestinal tract during oral administration. 98,135,[195][196][197] Oral delivery of nanoencapsulated quercetin with a size of 270 nm protects rat brain and liver cells from toxicity induced by arsenic. These studies have confirmed that quercetin is highly protected in the gastrointestinal tract and can be safely delivered to the target site in the brain.…”
Section: Nanoquercetinmentioning
confidence: 99%
“…It was reported that quercetin was able to maintain blood-brain barrier integrity by scavenging active oxygen (4). It was suggested that oral treatment with quercetin nanocapsules may exert a protective effect against oxidative damage and prevent pyramidal neurons in the hippocampus from ischemia/reperfusion (I//R) (5). However, the exact mechanism of the neuroprotective effect of quercetin against global brain I/R injury has remained elusive.…”
Section: Introductionmentioning
confidence: 99%